Prevalence of Gastrointestinal Protozoal Infections in Local Cats (Felis catus) in Harau District, Limapuluh Kota Regency - Rozaq, Muhammad Alwi; Amir, Yurni Sari; Zelpina, Engki; Siregar, Ramond (Universitas Airlangga, 2025)
Background: One disease that often affects cats' health is infection caused by viruses, bacteria, or protozoa. Protozoa are parasites that can live in the cat's digestive tract. Purpose: This study aims to determine the prevalence of digestive tract protozoa in local cats and determine the types of digestive tract protozoa that infect local cats in Harau District. This study also calculated the percentage of cats infected with protozoa based on the sex and age of the cat. Method: The examination method used in this research is the floating method. Examinations were carried out at the Animal Health and Disease Laboratory of the Payakumbuh State Agricultural Polytechnic on 50 feces samples from local cats kept in Harau District. Cat feces samples were taken using purposive sampling in Harau District. Results: The results of the examination showed that 7 out of 50 cat feces samples in Harau District tested positive for digestive tract protozoa with a prevalence of 14%. Two types of protozoa were found, namely Isospora spp. with a prevalence of 10%, Toxoplasma gondii 8% and double infections (Isospora spp and Toxoplasma gondii) with a prevalence of 4%. Based on the gender of cats infected with digestive tract protozoa, the percentage of male cats was 10.5% and female cats were 16.1%. Based on the age group of cats infected with digestive tract protozoa, the percentage was 20% in the kitten group (1-7 months), 15% in the juvenile group (7 months-2 years) and in the prime period group (2-6 years) none were positive. Conclusion: These findings highlight the presence and distribution patterns of protozoal infections in local feline populations, emphasizing the need for targeted preventive measures based on age and sex.